The remarkable genetic relationship between Staphylococcus aureus isolates from hemodialysis patients and their household contacts : Homes as an important source of colonization and dissemination (2022)
ABSTRACT : Introduction Staphylococcus aureus is a successful pathogen in hospital and community. Hemodialysis patients have high colonization rates. Interactions between them and their household contacts, are an opportunity to understand the S. aureus colonization between hospitals and community. This study aims to determine the clinical and epidemiological characteristics of S. aureus colonization in hemodialysis patients and their household contacts, as well as the genetic relationship between their isolates. Methods A cross-sectional study was conducted on hemodialysis patients from hospital-associated dialysis center in Medellın-Colombia, and their household contacts between 2019 and 2020. Colonization was assessed in the nostrils for household contacts and nostrils and skin around the catheter insertion for hemodialysis patients. Epidemiological information was obtained, and colonization was evaluated in their pets’ oral cavities. Bacterial identification and susceptibility were assessed using phenotypic and molecular methods. Molecular typing included SCCmec typing, pulsed-field gel electrophoresis (PFGE), spa typing, and virulence factor detection. Results Colonization frequency was 35.6% (n = 16/45) in patients (87.5% MSSA– 12.5% MRSA) and 43.1% (n = 53/123) in household contacts (88.7% MSSA—11.3% MRSA). Of 45 homes, 77.8% presented colonized people. Colonization was detected in at least two household members in 46.7% of homes, of which 52.4% had a genetic relationship. Colonization was 16% (n = 4/25) in pets (75% MRSA—25% MSSA). The most frequent clonal complex was CC8 (15.6%), and the spa typing revealed high diversity. Conclusion This study shows a high frequency of colonization by S. aureus in both hemodialysis patients and their household contacts and a significant genetic relationship between their isolates. This demonstrates an exchange of this bacterium and that homes are an important source of colonization to patients, highlighting the need for prevention strategies outside the hospital to avoid future infections, and the importance of the populations with permanent transit between the two environments.